Ultra-low-power plug-and-play sensor system for urban farming purposes / Muhammad Izzat Alif Muslan - Muslan, Muhammad Izzat Alif (2019)
Urban farming is a well-explored method of meeting the global food supply needs as the global population starts to shift into living in urban areas. To facilitate the growth of urban produce, a monitoring system is necessary. However, most existing monitoring systems tend to neglect the farmers in their operation by making the system too complex to operate without having the necessary technical skills. This study brings to the table a smart urban farming system that is easy to operate and install without being a direct party in the growth of the farm. By making the system plug-and-play, low power and independent, farm owners can easily install this system into a farm hassle-free while also allowing the system to operate for a long period of time. By using the Lorawan technology as a means of transmission, data from the sensors can be collected into a cloud database with long range and low power. This system was also a method of combating emerging pollutants from the excessive use of fertilizers by monitoring the amount of fertilizers used. The monitoring was achieved in a software developed using Keysight Vee. The use of new technology in pH detection, the 2-electrode cell used in this project to measure the amount of pH correlated with the fertilizers while being compact in size when compared with the conventional pH sensors. The device created in this project, dubbed the sensor pack, is a comprehensive Internet-of-Things gadget capable to be deployed out of the box, easily integrable and scalable. It was studied that the sensor pack drew current close to 80 uA on average in the span of a 5-minute cycle, making it ultra-low power. Further research in this area should include data analytics in order to optimize the yields of these urban farms even further.